Educational situation among blind students in Sulaimani University His research is qualitative at Sulaimani University - سعید, د. ئارام تۆفیق حمە; رەسول, تەلار جلال (Sulaimani Journal for Humanities, 2025)
Blindness is the most affecting form of disability, making it difficult to perform daily tasks. Especially for blind students, who lose an important source of knowledge with the loss of the visual sensor. However, Sulaimani University has blind students at all levels of undergraduate and graduate education. In this study, the educational situation of blind students is analyzed from the students' perspective. On three levels of learning problems, administrative problems such as traffic and buildings, and problems related to students' social relationships with classmates and teachers. The study is a qualitative study. Data were collected from blind students in Sulaimani University for the academic year 2024-2
Keywords: Disabled; blind; blind students; Sulaimani University